How can participatory design inform the design and development of innovative technologies for autistic communities? - Brosnan, Mark; Parsons, Sarah; Good, Judith; Yuill, Nicola (Journal of assistive technologies, 2016)
Purpose – The purpose of this paper is to reflect upon on the opportunities and challenges of engaging with a wide variety of stakeholders during the design, development and evaluation of innovative technologies for people with autism. Autism is defined in part by difficulties in social communication and interaction, and is therefore particularly pertinent when considering the opportunities and challenges of participatory design (PD). Design/methodology/approach – A series of presentations from key researchers and practitioners are reviewed, highlighting contemporary issues about how technologies have been designed to improve educational support using a range of methods and processes for stakeholder involvement. Findings – Involvement per se does not constitute engagement as a design partner. The interdisciplinary nature of PD, combined with the viewpoints of communities beyond academia, need to be integrated in a manner that allows for different perspectives and voices, and for the “trace” of the contribution to be evidenced. The level of evidence required for demonstrating effective support needs to be considered in terms of both the outcomes of projects and the processes for involving stakeholders in PD. Originality/value – This paper offers an up-to-date insight from lead researchers into key debates about the benefits and challenges of PD with autistic people and the broader autism community. Its value lies in raising questions about, and discussing evidence that challenges, some of the assumptions that underpin both PD processes and the needs of the autistic community.